2018
DOI: 10.1016/j.sleh.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep debt at the community level: impact of age, sex, race/ethnicity and health

Abstract: Although older adults may sleep less as they age, they may also require less sleep to feel rested, resulting in less sleep debt. This and other demographic factors, such as female gender and Hispanic/Latino ethnicity, can be used to identify those at higher risk of inadequate sleep and potentially manage their sleep debt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…For instance, studies have also found that sleep increased in quality and duration in older adults (Grandner et al, 2012;Ohayon et al, 2004). Moreover, a recent study conducted by Fox et al (2018) found that sleep debt (the cumulative effect of not getting enough sleep) actually decreased with age, counter to conventional wisdom that would mirror prior research that sleep gets worse as one ages (e.g. Ohayon et al, 2004).…”
Section: Disparities In Sleepmentioning
confidence: 94%
See 3 more Smart Citations
“…For instance, studies have also found that sleep increased in quality and duration in older adults (Grandner et al, 2012;Ohayon et al, 2004). Moreover, a recent study conducted by Fox et al (2018) found that sleep debt (the cumulative effect of not getting enough sleep) actually decreased with age, counter to conventional wisdom that would mirror prior research that sleep gets worse as one ages (e.g. Ohayon et al, 2004).…”
Section: Disparities In Sleepmentioning
confidence: 94%
“…However, based on previous findings (e.g. Durrence & Lichstein, 2006;Fox et al, 2018;Grandner et al, 2013;Krishnan & Collop, 2006), we expected to find that demographic factors differentially predicted sleep attitudes, and would interact with sleep attitudes in predicting sleep outcomes.…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Inadequate amount of sleep is a universal characteristic of contemporary culture. 1 Besides, insufficient sleep in healthcare workers can lead to medical errors and questions on the professional liability of those who were aware of their reduced sleeping hours. 2,3 The current article will explore some theories in healthcare organizations which unwillingly have conducted to altered sleep patterns in healthcare workers.…”
Section: Introductionmentioning
confidence: 99%